Analysis of water volume not sold due to failure of water pipelines - Studziński, Andrzej (Instal, 2019)
Failures of water pipes cause a number of losses, both for the supplier and for water consumers. For the water producer repairs of damaged pipelines are the most expensive. Other losses include losses resulting from the volume of water not sold to consumers. The study presents an analysis of the volume of these losses. The basis of the study are operational data taken for 298 failures in a medium-sized city located in southern Poland. In less than 9% of cases the repair was not carried out on the pipe under pressure, in other cases it was related to interruption of water supply to recipients. The failures presented concern the range of nominal diameters of 25-800 mm wires. The average number of recipients (water supply connections) affected by failure amounted to 19.5 and the average number of residents 117.1. The average volume of water not sold as a result of failure for 259 events was determined, 6.4 m3 for failure was obtained. The total volume of water not sold was only about 6% of average daily water production, so the losses can be determined as negligible.